596. The ID Physician Is Out: Are Remote ID E-Consults an Effective Substitute?. (4th December 2021) - Li, Sui Kwong; Fernandes, Carolyn; Nanjappa, Sowmya; Burgdorf, Sarah; Jagadeesan, Vidya; Knoll, Bettina; Khan, Shanza; Gupta, Nupur; Mellors, John; Abdel-Massih, Rima; Abdel-Massih, Rima
Abstract: Background: Telemedicine (TM) can provide specialty ID care for remote and underserved areas; however, the need for dedicated audio-visual equipment, secure and stable internet connectivity, and local staff to assist with the consultation has limited wider implementation of synchronous TM. ID e-consults (ID electronic consultations or asynchronous™) are an alternative but data are limited on their effectiveness, especially patient outcomes. Methods: In the setting of the COVID-19 pandemic and ID physician outage, we were asked to perform ID e-consults at a 380-bed tertiary care hospital located in Blair County, PA. We performed retrospective chart reviews of 121 patients initially evaluated by ID e-consults between April 2020 and July 2020. Follow-up visits were also conducted via e-consults with or without direct phone calls with the patient. Key patient outcomes assessed were length of stay (LOS), disposition after hospitalization, 30-day mortality from initial ID e-consult and 30-day readmission post-discharge. Results: The majority of patients were white males and non-ICU (Table 1). The most common ID diagnosis was bacteremia (27.3%, 33/121), followed by skin and soft tissue infections (15.7%, 19/121) and bone/joint infections (14.9%, 18/121) (Figure 1). Table 2 shows patient outcomes. Average total LOS was 11 days and 7 days post-initial ID e-consult. 48.7% (59/121) of patients were discharged home and 37.2% (45/121) to a post-acute rehabilitation facility. 2.5% (3/121) of patients required transfer to a higher level of care facility; none of which were to obtain in-person ID care. The index mortality rate was 3.3% (4/121), which appears to be lower than published data for in-person ID care. The 30-day mortality rate was 4.1% (5/121), which is also comparable to previously reported for ID e-consults. 25.6% (31/121) of patients required readmission within 30 days but only 14.0% (17/121) were related to the initial infection. Table 1. Demographics *Immunosuppressive agents include: Apremilast, Dasatinib, Etanercept, Remicade, Rituximab, and Prednisone >10 mg/day Figure 1. Variety of ID Diagnoses made by e-consults Table 2. Outcomes Conclusion: We believe that this is the first report of the implementation of ID e-consults at a tertiary care hospital. Mortality rates appear to be comparable to in-person ID care. In the absence of in-person ID physicians, ID e-consults can be a reasonable substitute. Further study is required to compare performance of ID e-consults to in-person ID consults. Disclosures: John Mellors, MD, Abound Bio, Inc. (Shareholder)Accelevir (Consultant)Co-Crystal Pharma, Inc. (Other Financial or Material Support, Share Options)Gilead Sciences, Inc. (Advisor or Review Panel member, Research Grant or Support)Infectious DIseases Connect (Other Financial or Material Support, Share Options)Janssen (Consultant)Merck (Consultant) Rima Abdel-Massih, MD, Infectious Disease Connect (Employee, Director of Clinical Operations) Rima Abdel-Massih, MD, Infectious Disease Connect (Individual(s) Involved: Self): Chief Medical Officer, Other Financial or Material Support, Other Financial or Material Support, Shareholder